2010
DOI: 10.1111/j.1365-3040.2010.02225.x
|View full text |Cite
|
Sign up to set email alerts
|

OsRAN2, essential for mitosis, enhances cold tolerance in rice by promoting export of intranuclear tubulin and maintaining cell division under cold stress

Abstract: With global climate change, abnormally low temperatures have affected the world's rice production. Many genes have been shown to be essential for molecular improvement of rice cold-tolerance traits. However, less is known about the molecular cellular mechanism of their response to cold stress. Here, we investigated OsRAN2 involved in regulation of cell division during cold stress in rice. Expression of OsRAN2 was increased under cold treatment, but not during salt and drought stress. The mean root mitotic inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
71
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 55 publications
3
71
0
1
Order By: Relevance
“…Our data are consistent with a previous report that OsRan2-overexpressing transgenic rice acquired cold resistance by maintaining cell division under stress conditions. 18) We observed that transgenic Arabidopsis with higher CLRan1 transgene expression (lines T6 and T11) exhibited enhanced root growth in both unstressed and PEG-stressed conditions ( Fig. 5(C)).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Our data are consistent with a previous report that OsRan2-overexpressing transgenic rice acquired cold resistance by maintaining cell division under stress conditions. 18) We observed that transgenic Arabidopsis with higher CLRan1 transgene expression (lines T6 and T11) exhibited enhanced root growth in both unstressed and PEG-stressed conditions ( Fig. 5(C)).…”
Section: Discussionmentioning
confidence: 74%
“…[11][12][13] In plants, Ran GTPase is encoded by small gene family in Arabidopsis. [14][15][16] Overexpression of Ran GTPase genes from wheat (TaRan1) and rice (OsRan2) resulted in an increase in the mitotic index in root apical meristems and enhanced growth in transgenic rice and Arabidopsis, 17,18) indicating that the function of Ran GTPase is strongly associated with meristem activity and cellular proliferation in plants. External stimuli such as cold stress 18) and jasmonic acid 19) are known to induce Ran GTPase expression in plants, but to the best of our knowledge, a connection between drought response and Ran GTPase in plants has not been described thus far.…”
mentioning
confidence: 98%
“…Recently, Endo et al [27] showed that OsCDKB2;1 (the same gene we identified) is involved in mitosis and DNA damage response in rice, which prevents delay mitotic cell-cycle progression in response to DNA damage checkpoints. Yet, Chen et al [28] over-expressed OsRAN2 gene, which is essential for mitosis and can promote intranuclear tubulin export at the end of mitosis. The transgenic rice plants maintained cell division under cold condition and enhanced cold tolerance (up to 80% survival, compared to 14% survival in WT plants).…”
Section: Differential Gene Expression Determinationmentioning
confidence: 96%
“…16 Use of RNAi to knockdown expression of RAN1 in rice cause significant growth changes including reduced viability, changes in the response to ABA/salt stress and cell cycle defects. 17,18 Opposingly, when RAN from rice or wheat is overexpressed either in its native plant or in Arabidopsis it causes a range of phenotypic changes. Overexpression of OsRAN1, TaRAN1 or OsRAN2 in rice causes resistance to cold stress, 18,19 while overexpression of TaRAN1 or OsRAN1 in Arabidopsis alters apical dominance and plant stature.…”
mentioning
confidence: 99%
“…17,18 Opposingly, when RAN from rice or wheat is overexpressed either in its native plant or in Arabidopsis it causes a range of phenotypic changes. Overexpression of OsRAN1, TaRAN1 or OsRAN2 in rice causes resistance to cold stress, 18,19 while overexpression of TaRAN1 or OsRAN1 in Arabidopsis alters apical dominance and plant stature. 19,20 Therefore given this breadth of information it is not surprising that when AtRAN1 is overexpressed in tobacco there is such a severe phenotype.…”
mentioning
confidence: 99%